Extracellular Vesicles: Tiny Messengers for Mighty RNA Delivery - Alakesh Das (Biologics, 2024)
Extracellular vesicles (EVs) encompass a diverse array of cell-derived vesicles, originating either from the endosomal compartment (exosomes) or generated through shedding from the cell membrane. These lipid bilayer nanovesicles carry a diverse cargo consisting of nucleic acids, various macromolecules, and growth factors, capable of being assimilated by nearby or distant cells through biofluids, thereby triggering a wide range of cellular responses. Given their distinctive biological characteristics and crucial roles in intercellular communication, EVs have garnered significant attention, especially concerning potential clinical applications. Inheriting cargo from their parent cells, EVs present promising resources for diverse disease biomarkers. Research elucidating the specific impacts of cargo on target cells has sparked enthusiasm for their therapeutic potential. Compelling evidence indicates that RNA cargo housed within EVs can modulate gene expression and influence cellular functions in recipient cells. However, despite significant progress, numerous aspects of EV biology remain obscure, encompassing selective cargo-loading mechanisms that yield distinct compositions from source cells, variability in size and content, and undisclosed pathways governing uptake and cargo fate in recipient cells. A thorough understanding of core EV mechanisms—such as generation, trafficking, and payload delivery—is essential for their effective clinical utilization. This review explores the current understanding of RNA loading and transportation within EVs, shedding light on the advancements made toward clinical applications.